Arbeitnehmerentsendung im Europäischen Binnenmarkt: Eine Analyse in international tätigen Unternehmen in Rheinland-Pfalz - Ruth Böck (Universität Trier, Institut für Arbeitsrecht und Arbeitsbeziehungen in der Europäischen Gemeinschaft (IAAEG), 1993)
An increasing number of enterprises is engaged in international markets. In order to be successful in these markets, enterprises are forced to base their personnel policy on stronger internationally orientated considerations. One instrument useful to realise this goal is to send employees to an establishment abroad. However, several problems might arise due to diverging interests and goals of employer and employees concerning the entry in the foreign enterprise. The study analyses how these problems are solved, i.e. whether individual contracts or collective agreements concluded between employer and works council are applied. The analysis is based on theoretical considerations as well as on the results of several case studies that have been conducted in enterprises in Rhineland-Palatinate. The analysis leads to the result that collective agreements are but exceptional cases. Existing regulations in this area nomally contain regulations concerning the selection, arrangements to prepare the stay abroad and the remuneration. The assistance abroad and the reintegration in the enterprises sending employees abroad are aspects being regulated less often. The results seem to indicate a correlation between the existence of such collective agreements and the number of employees, the number of establishrnents abroad, as well as the proportion of export. However, the existence of a works council seems to have no influence on the conclusion of regulations in this area. These results, as well as a discussion with experts have led to the following conlusion: the lack of information and knowledge on aspects to be negotiated between works council and employer results in only a few collective agreements being concluded in this area. In order to close this gap, an examplary agreement has been elaborated.
Keywords: 330